Isu Ketidakadilan Sosial dalam Konteks Masyarakat Multikultural di Indonesia Melalui perspektif Amsal 31:8-9 - Nando, Gideon; Faizal, Gan Matthew Iron; Kristianto, Adi Kurnia (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
This research examines the issue of social injustice within the context of Indonesia's multicultural society through the perspective of Proverbs 31:8-9. The background of the study highlights that, despite Indonesia's rich diversity in ethnicity, religion, and culture, challenges of intolerance and discrimination persist, particularly against minority groups. The aim of this research is to identify various forms of social injustice faced by Indonesian society and to analyze the insights from Proverbs 31:8-9 in providing solutions to these issues. The research employs a qualitative descriptive methodology, utilizing literature reviews and textual analysis. The findings indicate that the role of leaders is crucial in defending the rights of marginalized groups. Proverbs 31:8-9 emphasizes the moral responsibility of leaders to